Making family medicine work: Rural community-based and interprofessional medical education - Dirk T. Hagemeister (AOSIS, 2024)
At the University of the Free State, the 5-year MBChB curriculum had to be complemented with community-based education exposure to meet the requirements of the Health Professions Council of South Africa. Following the faculty leadership's vision, an interprofessional training experience was conceptualised and implemented by a project team from the three schools in the Faculty of Health Sciences (Medicine, Nursing, and Health and Rehabilitation Sciences). For the past decade, 4th-year medical students participated in the 2-week rotation in the rural southern Free State province, of which 1 week is spent with students from other health professions programmes in a structured interprofessional learning experience. The other week focuses on the realities of nurse-driven primary healthcare services in a resource-deprived area, including exposure to the programme-guided care for patients with tuberculosis (TB) or chronic diseases, care for pregnant women and for babies, including vaccinations.